Efficient energy harvesting of a GaN p–n junction piezoelectric generator through suppressed internal field screening. Issue 15 (29th March 2016) - Kang, Jin-Ho; Ebaid, Mohamed; Jeong, Dae Kyung; Lee, June Key; Ryu, Sang-Wan
Abstract : A high-efficiency GaN-based thin film piezoelectric energy harvester was demonstrated by suppressed screening of a piezoelectric field with the aid of a p–n diode junction. Abstract : A high-efficiency GaN-based thin film piezoelectric energy harvester was demonstrated by suppressed screening of a piezoelectric field with the aid of a p–n diode junction. Piezoelectric field screening was effectively controlled by the deposition of highly resistive p-type GaN. The semi-intrinsic property of Mg-doped GaN and improved junction quality successfully suppressed internal screening, which resulted in a significantly enhanced output voltage up to 8.1 V and a maximum output current density of 3.0 μA cm −2 . The energy-harvesting capabilities of the device were evaluated by charging a commercial capacitor, and self-powered light-emitting diode operation was demonstrated using the fabricated generator.